The role of interleukin-17 in vulvovaginal candidiasis (VVC): literature review - Rizka Amelia; Susilawati Susilawati; Fatmawati Fatmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Vulvovaginal candidiasis (VVC) is one of the most prevalent infections of the female genital tract. According to epidemiological data, almost 75% of women will at some point in their lives contract VVC. The main causative agent is Candida albicans. One of the main mediators is IL-17, a pro-inflammatory cytokine that is essential to the immunopathogenesis of VVC. Although IL-17 is essential for antifungal immunity, excessive or prolonged activation may lead to pathogenic inflammation and recurrence. This intricacy highlights the necessity of more research into the IL-17 regulation mechanisms in VVC and its possible use as a therapeutic target. Research published between 2020 and 2025 was included in a literature search that was done using databases including Scopus, PubMed, and Google Scholar. Eight of the 64 examined papers satisfied the requirements for inclusion. IL-17 is a key mediator in the immunopathogenesis of vulvovaginal candidiasis (VVC), according to preclinical, mechanistic, and clinical research. Treatments for VVC either increase or decrease IL-17 responses, and genetic variations in the IL-17/IL-23 axis are associated with a higher risk of developing the disease. In conclusion, IL-17 plays a key role in the pathophysiology of VVC. It is a promising biomarker and therapeutic target since it influences both immunological modulation and vulnerability through therapeutic treatments and genetic differences in the IL-17/IL-23 axis.